PENGARUH LOCUS OF CONTROL, KOMPETENSI, DAN KOMUNIKASI TERHADAP PEGAWAI UPTDK. RUMAH SAKIT UMUM HAJI MEDAN PEMERINTAH PROVINSI SUMATERA UTARA - Siregar, Nadhira Zahra; Siregar, Zulkarnain (Relawan Jurnal Indonesia, 2024)
This study aims to analyze the impact of locus of control, competence, and communication on employee performance at UPTDK Haji Hospital Medan. The methodology used is a quantitative approach with a simple random sampling technique, collecting data from 95 nurses. Data collection was carried out using SmartPLS version 4 and analysis was carried out using Structural Equation Modeling (SEM). The findings of this research indicate that locus of control, competence, and communication have a significant positive influence on employee performance. Furthermore, it was found that competence acts as a mediator in the relationship between locus of control and performance, which indicates partial mediation. In an organizational context, optimal employee performance is an indication of success, which is highly dependent on the management and development of human resources, where locus of control, competence and communication play an important role in improving performance.